Design of a Solar Powered Battery Charger - Adlina, Anis; Embong, Zaidi; Alias, Afishah (Enhanced Knowledge in Sciences and Technology, 2023)
Renewable energy sources include biomass power, wind power,hydroelectricity and most widely used is solar energy. Solar energy may be capturedby utilising a solar panels, which directly turns sunlight into electrical energy. Manytiny electrical equipment, such as battery chargers, can also benefit from solarelectricity. A solar-powered battery charger for a motorised wheelchair is constructedin this project to charge lead acid batteries and signal the user when the batteries arefully charged. One of the least expensive ways to charge batteries is the main benefitof using a solar-powered battery charger. In addition, solar powered battery chargersare quickly gaining acceptance since they have been shown to be useful in a varietyof settings, particularly in the outdoors, as well as being user friendly and portable. Aconstant current source is employed to replenish the batteries in this project, and thecapacitance of the lead acid battery is successfully measured. When the batteries havebeen fully charged, an LED light bulb will activate to notify the user that the batteriesmay now be utilised.